Network connectivity performance for vehicular Ad Hoc networks based on channel transmission environment - Yang LI; Haitao ZHAO; Zihao TANG; Yuting ZHANG (Dianxin kexue, 2016)
The inter-vehicle transmission interference is one of the key factors to impact the communication performance of vehicular Ad Hoc networks. When vehicles send signals at the same time, it will inevitably have an impact on the surrounding vehicles, which has a negative effect on network connectivity prediction. According to vehicle density and traffic flow, a vehicular network connectivity prediction model was presented based on Nakagami distribution. The Nakagami distribution was used to describe the fading channel in the signal transmission process. Form expression of the inter-vehicle connectivity probability was also derived with power probability density function and signal to noise ratio of received signals.Simulation results show that connectivity probability can be well improved with larger ratio of vehicles which transmit signals before the ratio reaches the maximum.However,negative effect will take place on vehicular connectivity when the ratio exceeds the maximum value.